(untitled) (Asian-Australasian Journal of Food Safety and Security, 2021)
A study was investigated to estimate the current status of health hazardous organochlorine insecticide DDT and its metabolites DDE and DDD in different species of dry fish. To achieve the goal of this experiment, ten different sun-dried fish samples were collected from different markets of Dhaka city. The concentration of DDT, DDE and DDD was determined using the capillary column coupled to Gas Chromatograph with Electron Captured Detector (GC-ECD). Most of the dry fishes, seven out of ten samples, were found to be contaminated with DDT along with its metabolites DDE and DDD ranging from 0.029-1.22 mg/kg which is a serious concern because of the nature of long persistency and bioaccumulation of DDT in the environment. The highest concentration of DDT (1.22 mg/kg) was observed in Pampus chinensis dry fish whereas low concentration was detected in Otolithoides pama (0.029 mg/kg). Asian Australas. J. Food Saf. Secur. 2021, 5 (2), 79-84